Prosedur Pelaksanaan Pelatihan Tentang Keselamatan Kerja Dan Lingkungan Di Telkom Witel Denpasar - Ananda Putra, I Gusti Agung; Ni Luh Utari Liana Sari (LPPM Universitas HKBP Nommensen, 2025)
Field Work Practice (PKL) has been carried out at Telkom Witel Denpasar from June 10 to August 9, 2024. This report discusses the procedures for implementing training on occupational safety and the environment at Telkom Witel Denpasar. Procedures related to occupational safety and the environment have been prepared but have not been realized in detail. With the procedures and understanding directly related to emergency response not yet being realized, training is needed to increase employee awareness and comply with existing regulations. The main objective of this activity is to provide understanding and provide knowledge about emergency response procedures related to occupational safety and the environment. With these problems, surveys and interviews were conducted in the field. Then, there is a method of implementation, namely conducting training related to occupational safety and the environment to increase awareness and practice of occupational safety and environmental management in the company. The training that has been carried out includes the use of personal protective equipment, fire and emergency evacuation simulations, emergency response procedures, handling hazardous materials, and waste management. The results of the implementation of this training show a significant increase in employee awareness, understanding, knowledge and the realization of established procedures which are expected to reduce the number of work accidents, reduce negative impacts on the environment and ensure compliance with applicable regulations.